Glossina pallidipes Density and Trypanosome Infection Rate in Arba Minch Zuria District of Gamo Zone, Southern Ethiopia - Ephrem Tora; Wasihun Seyoum; Firew Lejebo (Journal of Parasitology Research)
Background. African trypanosomosis is a disease of both animals and humans resulting from infection with parasitaemic protozoa of the genus Trypanosoma transmitted mainly by the tsetse flies (Glossina species). The disease has been reported in different parts of the country. However, information on the apparent density and trypanosome infection rates of the vectors is very limited in the Southern part of Ethiopia. Therefore, this study was conducted to estimate the apparent density, infection rate of trypanosomes in Glossina pallidipes, and the trypanosome species involved in Arba Minch Zuria district of Southern Ethiopia. Methods. A cross-sectional study was conducted from January to June 2018 in two purposely selected kebeles of Arbaminch Zuria district and in the escarpments of Nech Sar National Park of Southern Ethiopia. For entomological survey, a total of 40 standard NGU traps were deployed around the watering and grazing areas. A total of 300 fresh Glossina pallidipes were examined for trypanosome infection using a dissection procedure as described by the FAO Training manual for tsetse control personnel. Results. The study revealed the presence of only one Glossina species, known as Glossina pallidipes, and biting flies including Stomoxys and Tabanus. A total of 2176 flies were caught of which 1803 (82.86%) belong to Glossina pallidipes and the remaining 373 (17.14%) were biting flies. The overall apparent density of Glossina pallidipes and biting flies in the study area were 15.03 fly/trap/day (F/T/D) and 3.11 F/T/D, respectively. Relatively higher Glossina pallidipes and biting flies, respectively, were caught in a wood-grass land (15.87 F/T/D and 3.69 F/T/D) and riverine forest (15.13 F/T/D and 3.42 F/T/D) than bush land vegetation types (13.87 F/T/D and 1.76 F/T/D). The overall trypanosome infection rate of Glossina pallidipes was 17.67% (53/300). Two trypanosome species, namely, Trypanosoma congolense (66.04%) and Trypanosoma vivax (33.96%), were responsible for Glossina pallidipes infection in the study area. Trypanosome infection rate was significantly higher in female G. pallidipes than in male (OR=3.39, 95%CI=1.53‐7.52). Significantly, higher trypanosome infection rate was observed in flies older than 20 days (OR=2.5, 95%CI=1.12‐5.56) and in hunger stage 1 flies (OR=14.24, 95%CI=4.01‐50.59). Glossina pallidipes infection was significantly higher in and around park grazing areas (OR=3.41, 95%CI=1.76‐6.6) and wood-grass land vegetation type (OR=2.7, 95%CI=1.2‐6.5). Conclusion. The current study revealed high apparent density and trypanosome infection in Glossina pallidipes in Arba Minch Zuria district of Southern Ethiopia. So, this study warrants the need for strengthening both vector and parasite control strategies in the study area.